Forest residue removal undermines soil health and micronutrient transfer to trees, compromising sustainable productivity of Eucalyptus plantations - Antonio L. Florentino; Nariane de Andrade; Nikolas S. Mateus; Bruna E. Schiebelbein; Adam C. Rodrigues; Liamara S. Masullo; Alexandre V. Ferraz; Eduardo Mariano; Fernando D. Andreote; Carlos E.P. Cerri; Maurício R. Cherubin; Timothy R. Filley; et al. (Soil and Tillage Research, 2026)

Twelve-year residual effect of sewage sludge on the biogeochemical cycling of potentially toxic elements in tropical Eucalyptus plantation - Antonio L. Florentino; Alexandre V. Ferraz; Adam C. Rodrigues; Nikolas S. Mateus; Paulo H.S. Cardoso; Timothy R. Filley; Eduardo Mariano; José Lavres; José L.M. Gonçalves; Cassio H. Abreu-Junior (Forest Ecology and Management, 2025)

Invasive Japanese beetle (Popillia japonica Newman) larvae alter structure and carbon distribution in infested surface soil - Gordon R. MacLeod; Douglas S. Richmond; Timothy R. Filley (Science of The Total Environment, 2024)

Seasonal differences in trace metal concentrations in the major rivers of the hyper-arid southwestern Andes basins of Peru - Alexander Ccanccapa-Cartagena; Francisco D. Chavez-Gonzales; Betty Paredes; Corina Vera; Guillermo Gutierrez; Roland Valencia; Ana Lucia Paz Alcázar; Nadezhda N. Zyaykina; Timothy R. Filley; Chad T. Jafvert (Journal of Environmental Management, 2023)

Spartina alterniflora invasion differentially alters microbial residues and their contribution to soil organic C in coastal marsh and mangrove wetlands - Xueli Ding; Weiqi Wang; Jiahui Wen; Tianshu Feng; Josep Peñuelas; Jordi Sardans; Chao Liang; Evgenios Agathokleous; Chun Wang; Zhaoliang Song; Qiang Li; Timothy R. Filley; et al. (CATENA, 2023)

Storm pulse responses of fluvial organic carbon to seasonal source supply and transport controls in a midwestern agricultural watershed - Tingyu Hou; Neal E. Blair; A.N. Thanos Papanicolaou; Timothy R. Filley (Science of The Total Environment, 2023)

Warming yields distinct accumulation patterns of microbial residues in dry and wet alpine grasslands on the Qinghai-Tibetan Plateau - Xueli Ding; Shengyun Chen; Bin Zhang; Hongbo He; Timothy R. Filley; William R. Horwath (Biology and Fertility of Soils, 2020)

Conversion of grassland into cropland affects microbial residue carbon retention in both surface and subsurface soils of a temperate agroecosystem - Xueli Ding; Bin Zhang; Zhanbo Wei; Hongbo He; Timothy R. Filley (Biology and Fertility of Soils, 2020)

Changes of microbial residues after wetland cultivation and restoration - Xueli Ding; Bin Zhang; Timothy R. Filley; Chunjie Tian; Xudong Zhang; Hongbo He (Biology and Fertility of Soils, 2019)

Validation of PyMBMS as a High-throughput Screen for Lignin Abundance in Lignocellulosic Biomass of Grasses - Bryan W. Penning; Robert W. Sykes; Nicholas C. Babcock; Christopher K. Dugard; John F. Klimek; David Gamblin; Mark Davis; Timothy R. Filley; Nathan S. Mosier; Clifford F. Weil; Maureen C. McCann; Nicholas C. Carpita (BioEnergy Research, 2014)

Coupled response of soil carbon and nitrogen pools and enzyme activities to nitrogen and water addition in a semi-arid grassland of Inner Mongolia - Ruzhen Wang; Timothy R. Filley; Zhuwen Xu; Xue Wang; Mai-He Li; Yuge Zhang; Wentao Luo; Yong Jiang (Plant and Soil, 2014)

Biomimetic oxidative treatment of spruce wood studied by pyrolysis–molecular beam mass spectrometry coupled with multivariate analysis and 13C-labeled tetramethylammonium hydroxide thermochemolysis: implications for fungal degradation of wood - Valdeir Arantes; Yuhui Qian; Stephen S. Kelley; Adriane M. F. Milagres; Timothy R. Filley; Jody Jellison; Barry Goodell (JBIC Journal of Biological Inorganic Chemistry, 2009)

Sources of plant‐derived carbon and stability of organic matter in soil: implications for global change - SUSAN E. CROW; KATE LAJTHA; TIMOTHY R. FILLEY; CHRISTOPHER W. SWANSTON; RICHARD D. BOWDEN; BRUCE A. CALDWELL (Global Change Biology, 2009)
Alterations in forest productivity and changes in the relative proportion of above‐ and belowground biomass may have nonlinear effects on soil organic matter (SOM) storage. To study the influence of plant litter inputs on SOM accumulation, the Detritus Input Removal and Transfer (DIRT) Experiment continuously alters above‐ and belowground plant inputs to soil by a combination of trenching, screening, and litter addition. Here, we used biogeochemical indicators [i.e., cupric oxide extractable lignin‐derived phenols and suberin/cutin‐derived substituted fatty acids (SFA)] to identify the dominant sources of plant biopolymers in SOM and various measures [i.e., soil density fractionation, laboratory incubation, and radiocarbon‐based mean residence time (MRT)] to assess the stability of SOM in two contrasting forests within the DIRT Experiment: an aggrading deciduous forest and an old‐growth coniferous forest. In the deciduous forest, removal of both above‐ and belowground inputs increased the total amount of SFA over threefold compared with the control, and shifted the SFA signature towards a root‐dominated source. Concurrently, light fraction MRT increased by 101 years and C mineralization during incubation decreased compared with the control. Together, these data suggest that root‐derived aliphatic compounds are a source of SOM with greater relative stability than leaf inputs at this site. In the coniferous forest, roots were an important source of soil lignin‐derived phenols but needle‐derived, rather than root‐derived, aliphatic compounds were preferentially preserved in soil. Fresh wood additions elevated the amount of soil C recovered as light fraction material but also elevated mineralization during incubation compared with other DIRT treatments, suggesting that not all of the added soil C is directly stabilized. Aboveground needle litter additions, which are more N‐rich than wood debris, resulted in accelerated mineralization of previously stored soil carbon. In summary, our work demonstrates that the dominant plant sources of SOM differed substantially between forest types. Furthermore, inputs to and losses from soil C pools likely will not be altered uniformly by changes in litter input rates.

Fungal diversity and deterioration in mummified woods from the ad Astra Ice Cap region in the Canadian High Arctic - Joel A. Jurgens; Robert A. Blanchette; Timothy R. Filley (Polar Biology, 2009)